Rocks rock: the importance of rock formations as resting sites of the Eurasian lynx Lynx lynx. Issue 1 (27th March 2019) - Signer, Johannes; Filla, Marc; Schoneberg, Sebastian; Kneib, Thomas; Bufka, Ludek; Belotti, Elisa; Heurich, Marco
Abstract : Eurasian lynx Lynx lynx L. are recolonizing parts of their former range in Europe. Not only are lynx strictly protected as a species, but also their habitat and in particular their resting sites are protected. As the known characteristics of lynx resting sites are restricted to vegetation structure, it is difficult to take resting sites into account in planning processes. Here, we show the importance of rock formations for potential resting sites selection and analyzed the frequencies at which GPS‐collared lynx returned to potential resting sites in the Bohemian Forest Ecosystem at the border between the Czech Republic and Germany. Lynx showed a strong selection for proximity of rocks for resting site selection, and the distance of potential resting sites to rocks was an important predictor for determining whether lynx return to the resting site or not. Furthermore, the frequency of returns to the resting site was positively influenced by the distance to roads and geomorphology. Our findings highlight the importance of rock formations as resting sites for lynx, which can help with the implementation of concrete protection measures.